PENGARUH DANA PIHAK KETIGA, CAPITAL ADEQUACY RATIO DAN NON PERFOMING LOAN TERHADAP PEMBERIAN KREDIT PADA PERUSAHAAN PERBANKAN KONVENSIONAL DI BURSA EFEK INDONESIA - Zusmawati Zusmawati; Yuliza Rahmi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
Loans are loans or bills agreed between parties. This study aims to determine the effect of third party funds, capital adequacy ratio and non perfoming loanon gifts to banking companies on the Indonesia Stock Exchange. Source of data used in this study is secondary data in the form of annual reports. The population used in this study are all banking companies listed on the Indonesia Stock Exchange (IDX) in the 2015-2019 period that were selected using purposive sampling techniques. The number of samples used in the study were 35 companies. The analytical method used is multiple regression analysis. Based on the test results it was found that Third Party Funds (DPK) had a positive and significant effect on lending to banking companies on the Indonesia Stock Exchange, while the Capital Adequacy Ratio (CAR) and Non Performing Laon (NPL) had no effect on lending to banking companies in Indonesia stock exchange.